Performance of Rental Values of Residential Properties in Selected areas in Akure, Nigeria between 2001 and 2011 - Amietsenwu, Bello Victoria (Richtmann Publishing, 2012)
The paper examined changes in rental values of residential properties in two neighbourhoods (Oke – Ijebu and Apatapiti) inAkure from 2001 to 2011. The intent is to provide a measure of the performance of this sector in the past years. Questionnaires wereadministered on 14 registered Estate Surveyors and Valuers practicing in Akure out of which 11 were returned and good for analysis.The returned questionnaires were analysed using the Trend Analysis and regression model for the computation of growth rate. Thefindings indicated that rental value of 3 Bedroom flat and tenement accommodation have been on the increase since 2001 to 2011especially with Apatapiti neighbourhood having higher rental values than Oke – Ijebu. The result also showed the growth rates of 3bedroom flat and tenement accommodation in Oke Ijebu to be 38.44% and 43.07% respectively as against 23.15% and 34.98% for 3bedroom and tenement accommodation in Apatapiti area. It is therefore, recommended that the federal government should build morehostels in the Federal University of Technology Akure which is close to Apatapiti one of the study areas. This gesture will help to lessenthe burden on accommodation especially in Apatapiti thereby, reducing the undue advantage taken by landlords in increasing rents.